2008
DOI: 10.1002/hep.22400
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic role of natural killer T and natural killer cells in acetaminophen-induced liver injury in mice is dependent on the presence of dimethyl sulfoxide

Abstract: Dimethyl sulfoxide (DMSO) is commonly used in biological studies to dissolve drugs and enzyme inhibitors with low solubility. Although DMSO is generally thought of as being relatively inert, it can induce biological effects that are often overlooked. An example that highlights this potential problem is found in a recent report demonstrating a pathogenic role for natural killer T (NKT) and natural killer (NK) cells in acetaminophen-induced liver injury (AILI) in C57Bl/6 mice in which DMSO was used to facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 48 publications
4
83
1
Order By: Relevance
“…The drug was started at Day 0, and injection of anti-NK1.1 antibody, IgG 1 isotype, or PBS was repeated every week to maintain suppressed NK activity (Koo et al, 1986). Administration of this anti-NK1.1 antibody has been previously shown to deplete NK and NKT cells (Masson et al, 2008). In our laboratory, injection with anti-NK1.1 antibody depletes NK and NKT cells in the liver, spleen, blood, and cervical lymph nodes; depletion of NK cells was also confirmed by staining with anti-NKP46 antibody (another cellular marker for NK cells; data not shown).…”
Section: Natural Killer Cell Depletionsupporting
confidence: 56%
“…The drug was started at Day 0, and injection of anti-NK1.1 antibody, IgG 1 isotype, or PBS was repeated every week to maintain suppressed NK activity (Koo et al, 1986). Administration of this anti-NK1.1 antibody has been previously shown to deplete NK and NKT cells (Masson et al, 2008). In our laboratory, injection with anti-NK1.1 antibody depletes NK and NKT cells in the liver, spleen, blood, and cervical lymph nodes; depletion of NK cells was also confirmed by staining with anti-NKP46 antibody (another cellular marker for NK cells; data not shown).…”
Section: Natural Killer Cell Depletionsupporting
confidence: 56%
“…The role of the innate immune response activated through APAP-induced direct hepatocyte death in animal models also remains controversial (13). Many cell types have been implicated in determin-ing the extent of organ injury or regeneration in the liver, such as Kupffer cells (14), neutrophils (15), natural-killer cells and natural-killer cells with T-cell receptor (16).…”
Section: Introductionmentioning
confidence: 99%
“…While the basis for the contradictory results in JNK2 −/− mice susceptibility to AILI is not clear, different doses of APAP were used in each study, which might affect the results, and in one case, APAP was dissolved in DMSO [21], which is known to have a profound effect on APAP metabolism [33] and innate-immune response after APAP [34]. Nevertheless, it remains to be determined whether these factors contribute to the conflicting findings.…”
Section: Discussionmentioning
confidence: 99%
“…Potential limitations of these studies, as acknowledged by the investigators [21,22] is that JNK inhibitors may not be specific and as reported can affect other signaling events that could lead to the misinterpretation of results [36][37][38][39]. Further, some of the JNK inhibitors were dissolved in vehicles containing DMSO [14,21] and polyethylene glycol [22,35], which may affect various parameters at the cellular and molecular level [34,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation